Acculturation is associated with older Turkish immigrants' self-management abilities - Jane M. Cramm; Anna P. Nieboer (BMC, 2019)
Abstract Background The few previous studies investigating acculturation and self-management have suggested that increased participation in (or adaptation to) the host culture is associated with better health and disease management. However, research on the relationship between acculturation strategies (attachment to the Dutch and Turkish cultures) and broader self-management abilities among older Turkish immigrants in the Netherlands is lacking. This study aimed to investigate this relationship in this population. Methods Turkish immigrants aged > 65 years and residing in Rotterdam, the Netherlands (n = 2350), were identified using the municipal register. In total, 680 respondents completed the questionnaire (32% response rate). Results The average age of the respondents was 72.90 (standard deviation, 5.02; range, 66-95) years and 47.6% of respondents were women. The majority (80.3%) of respondents reported having low educational levels. Women, single individuals, less-educated respondents, and those with multimorbidity experienced lower levels of attachment to the Dutch culture and reported poorer self-management abilities. Slightly stronger relationships were found between self-management and attachment to the Dutch culture than attachment to the Turkish culture. Multimorbidity negatively affected the self-management abilities of older Turkish people living in the Netherlands. Conclusions The study findings indicate that especially attachment to the Dutch culture matters for the self-management abilities of older Turkish immigrants in the Netherlands. Given the high prevalence of multimorbidity in this population, investment in their self-management abilities is expected to be beneficial. Special attention is needed for women, single individuals, less-educated people, and those with multimorbidity. Interventions aiming to better integrate these groups into Dutch society are also expected to be beneficial for their self-management abilities.